UJI LAMA PERENDAMAN STEK LADA (PIPER NIGRUM L) PADA EKTRAK TAUGE TERHADAP PERTUMBUHAN AKAR DAN TUNAS - Murdaningsih Murdaningsih; Philipus Nerius Supardi; Fransiskus Soge (AGRICA, 2019)
The study was intended to determine the growth response of the pepper plant steak due to an extended 3 hours of Tauge extracting with a concentration of 300 ml/l. The design used in this study is a completely random design with a single factory based pattern of P1 (1 hour), P2 (2 hours), P3 (3 hours), P4 (4 hours), P5 (5 hours). Variable observations in this study are the number of shoots (strands), length of shoots (cm2), number of leaves (strands), amount of roots (cm2), length of roots (cm2), fresh shoots (gram), shoots dry weights (gram), root fresh weights (gram), root dry weights (gram), root dry weights (gram). Studies indicate that extended snorting time of pepper on and Tauge extracting gives very real influence to the growth variable of sprouts (50,66%), root length (32,96%), leaves (58,88%), root length (45,14%), root weight (57,72%), shoots (71,43%), shoots dry weight (65,73%). Thus the treatment of Tauge extracts as one of the natural growth regulator plants in seeding with a concentration of 300 m/l water would be best submerged for 3 hours to speed up the growth and remove the roots to achieve the best quality of the steed growth.